COVID-19: considerations for the safe management and disposal of human excreta (2020)
Management and disposal of human excreta is an essential element of healthcare practice. The potential for cross transmission of SARS-CoV-2 in faeces and urine has led global healthcare providers to examine different infection prevention and control practices not least the management and disposal of human excreta. There are two major systems in place to undertake this; one being the use of reusable bedpans and urinals with reprocessing in a washer disinfectors (WD). The other is use of disposable system; either with pulp bedpans and urinals disposed of in a macerator or hygienic bags disposed of as waste. A review of the literature provided limited evidence to explore these different methods; both having pros and cons with regards to the environmental aspects as well as the infection prevention and control implications. Manual cleaning can pose associated infection risks to both staff and patients. Disinfection of re-usable bedpans may not achieve the level of disinfection required. Disposable systems offer an alternative that can overcome some of the infection prevention and control limitations of washer disinfectors. Adherence to infection prevention and control standards are paramount to the safe management and disposal of excreta.